Implementation of Tourism Place Branding Management in Indonesia through the 'Wonderful Indonesia' Campaign - Mutma, Fasya Syifa; Dyanasari, Reni (Journal of Communication and Public Relations, 2025)
Tourism has become a significant sector in Indonesia's economy since 2019. Indonesia has a tourism brand managed by the Ministry of Tourism and Creative Economy (Kemenparekraf) called "Wonderful Indonesia." Since its launch in 2011 and its promotion in 2015 until the present, Indonesian tourism, especially the Wonderful Indonesia brand, has received various national and international awards. These accolades can be attributed to the marketing communication and branding efforts carried out by Kemenparekraf. There is a concept called place branding, where "Wonderful Indonesia" is applied to brand Indonesian tourism. This research aims to understand the implementation of the tourism place branding concept in the marketing communication and branding efforts of Wonderful Indonesia. This research utilizes integrated marketing communication, branding, and place branding. The research adopts a constructivist paradigm with a qualitative descriptive method. Data collection involved interviewing representatives from Kemenparekraf who were involved in marketing communication and branding activities for Wonderful Indonesia. The data was then coded and analyzed. The research findings reveal that Kemenparekraf employs marketing communication strategies, incorporating Integrated Marketing Communication (IMC) components, and implements branding in line with the place branding concept. The study identifies that the branding implementation fulfills the 10 Strategic Place Brand Management Model components: brand infrastructure, stakeholder management (engagement), brand leadership, articulation, architecture, communication, identity, experience, word-of-mouth, and evaluation. Kemenparekraf also effectively implements an integrated marketing communication (IMC) approach by utilizing various tools, such as advertising, promotion, sponsorships, marketing events, experiential marketing, product placement, branded content, packaging, trade shows and fairs, personal selling, direct marketing, and public relations.